Lithic raw material use around the Inner Sound (Scottish Historical and Archaeological Internet Reports, 2009)
As a part of the project major sources of raw material were visited and the surveyors collected and recorded any nodule material that they found. In addition, walks were made across some of the beaches in the study area in order to look for nodules of suitable materials but little was found. It soon became clear that detailed work on the lithic raw material would involve the individual classification of every archaeological piece by a specialist, and thus be lengthy and expensive. In the event, basic differentiation was done by eye by the author. There is scope for more precise geological work to be done in the future. The analysis of the use of lithic raw material has much to offer the wider picture of prehistoric activity in the area.